Molecular characterization of 39 de novo sSMC: contribution to prognosis and genetic counselling, a prospective study. (5th April 2013) - Marle, N.; Martinet, D.; Aboura, A.; Joly‐Helas, G.; Andrieux, J.; Flori, E.; Puechberty, J.; Vialard, F.; Sanlaville, D.; Fert Ferrer, S.; Bourrouillou, G.; Tabet, A.C.; et al.
<x xml:space="preserve">Abstract</x> Small supernumerary marker chromosomes (sSMCs) are structurally abnormal chromosomes that cannot be characterized by karyotype. In many prenatal cases of de novo sSMC, the outcome of pregnancy is difficult to predict because the euchromatin content is unclear. This study aimed to determine the presence or absence of euchromatin material of 39 de novo prenatally ascertained sSMC by array‐comparative genomic hybridization (array‐CGH) or single nucleotide polymorphism (SNP) array. Cases were prospectively ascertained from the study of 65, 000 prenatal samples [0.060%; 95% confidence interval (CI), 0.042–0.082]. Array‐CGH showed that 22 markers were derived from non‐acrocentric markers (56.4%) and 7 from acrocentic markers (18%). The 10 additional cases remained unidentified (25.6%), but 7 of 10 could be further identified using fluorescence in situ hybridization; 69% of de novo sSMC contained euchromatin material, 95.4% of which for non‐acrocentric markers. Some sSMC containing euchromatin had a normal phenotype (31% for non‐acrocentric and 75% for acrocentric markers). Statistical differences between normal and abnormal phenotypes were shown for the size of the euchromatin material (more or less than 1 Mb, p = 0.0006) and number of genes (more or less than 10, p = 0.0009). This study is the largest to date and shows the utility of array‐CGH or SNP array in the detection and characterization of de novo sSMC in a prenatal context.